Transestrification Reactions for the Production of Biodiesel from Chicken Wastes (Journal of Pure & Applied Sciences, 2018)
The objective of this work is to employ chicken fat as a feedstock for the production of biodiesel by transesterification reaction using methanol, and alkali catalyst such as KOH. The experimental part presents a method to recover fat from the chicken wastes (skin) and convert triglycerides to methyl ester. The reaction progression was checked and characterised by IR spectroscopic method. The physicochemical properties such as; pour point, flash point, specific gravity, aniline point and viscosity of biodiesel was measured. The obtained results were principally consistent with previous results of other reports and with biodiesel international standards (EN-14214) and ASTM standards for petroleum gasoil.